Synthesis and telomeric G-quadruplex-stabilizing ability of macrocyclic hexaoxazoles bearing three side chains - Ma, Yue (2019)
G-quadruplexes (G4s), which are structures formed in guanine-rich regions of DNA, are involved in a variety of significant biological functions, and therefore “sequence-dependent” selective G4-stabilizing agents are required as tools to investigate and modulate these functions. Here, we describe the synthesis of a new series of macrocyclic hexaoxazole-type G4 ligand (6OTD) bearing three side chains. One of these ligands, 5b, stabilizes telomeric G4 preferentially over the G4-forming DNA sequences of c-kit and K-ras, due to the interaction of its piperazinylalkyl side chain with the groove of telomeric G4.